Low-intensity transcranial ultrasound stimulation facilitates hand motor function and cortical excitability: A crossover, randomized, double blind study - Zhang, Meng-Fei; Chen, Wei-Zhou; Huang, Fub-Biao; Peng, Zhi-Yong; Quan, Ying-Chan; Tang, Zhi-Ming (Frontiers in Neurology, 2022)
Objective: The effect of low-intensity transcranial ultrasound (TUS) on the physiological activity of the motor cortex and its potential application in a therapeutic context have not been extensively investigated. We aimed to investigate the effect of low-intensity TUS on hand reaction responses and cortical excitability in healthy adults. Methods: This study used A crossover, randomized, double blind study. A total of 20 healthy participants were recruited for the study. All the participants received TUS and sham stimulation on separate days in a random order. The finger tapping test (taping score by using ipad) and motor evoked potential (MEP) were assessed before and after stimulation, and discomfort levels were assessed using a visual analogue scale (VAS) score. Results: No significant differences in tapping score, and MEP amplitude between the two experimental conditions were registered before stimulation. After stimulation, tapping score were increased regardless of the specific treatment, and the real stimulation condition receiving TUS (90.4±11.0 points) outperformed the sham stimulation condition (86.1 ± 8.4 points) (P = 0.002). The MEP latency of real TUS (21.85 ± 1.33 ms) was shorter than that of sham TUS (22.42 ± 1.43 ms) (P < 0.001). MEP amplitude of real TUS (132.18 ± 23.28 μV) was higher than that of sham TUS (114.74 ± 25.5μV, P = 0.005). There was no significant difference in the discomfort score between the two conditions (P =0.163). Conclusion: TUS can decrease the hand reaction response time and latency of the MEP, enhance the excitability of the motor cortex, and improve hand function in healthy individuals without obvious discomfort.